Prevalence of Refractive Errors in Children of Parents with Consanguinity, in an Eye Camp in a Rural Area - Tahir Mahmood Khan, Zahid Mahmood, M. Anwer Awan, Anwaar Ul Haq Hashmi, Laiba Randhawa, Aima Raza Bukhari, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Early detection makes refractive error treatable. The risk of refractive errors and other congenital disorders is increased by consanguinity. Early screening can prevent lifelong morbidity and decrease family burden. Aims and Objectives: As is acknowledged by most of previous researchers, Refractive errors are more common in children from parental cousin marriage. It is for further strengthen background concept and reality so that this study was conducted. Study Design: In 2023, Current analytical cross sectional study was conducted on patients coming in four days eye camp at village Minhala, near Lahore Jallo Morh. Methodology: A total number of 1449 patients were examined. The total 632 School going children was from 8-16 years of age. Of these 446 children, there were parents of consanguinity. We now selected only those children (n=386) whose parents have consanguinity and ametropia. It was filled according to the proforma. Snellen’s Chart was used to perform Visual acuity. If found, refractive error was corrected and nature of error was also mentioned. SSP version 23 was used to analyse data. Qualitative data was presented in Frequency and Percentages, and Quantitative data was presented using (Mean ±SD). We used chi square test to determine whether types of refractive errors were associated with age group and gender. Mean standard deviations were considered significant (P<0.05). Results: The results confirm that children from consanguineous families have a significantly (p < 0.05) greater burden of refractive errors, especially for myopia, than children from non-consanguineous families. This emphasizes the importance of screening and intervention programs focused on the population with high consanguinity rates. Conclusion: Children from consanguineous families had a greater frequency of refractive errors, according to the study, highlighting the importance of focused screening and eye care. These therapies can lessen vision impairment while promoting the social and academic growth of kids. Keywords: Consanguineous, Consanguinity, retina, Vision